Adherence to physical activity in patients with coronary artery disease [Adherence k pohybové aktivitě u pacientů s kardiovaskulárním onemocněním] - Hana Cipryanová; Václav Krejčíř; Olga Hynková; Miloslav Klugar; Eliška Sovová; Jan Bajorek; Pavel Stejskal; Veronika Drbošalová (Palacky University, 2010)
OBJECTIVE: The aim of this study was to evaluate the adherence to a physical activity (PA) in an annual interventional programme of domiciliary rehabilitation designed for patients with coronary artery disease. METHODS: The final group consisted of 20 patients (4 women and 16 men) from the 1st Internal Department - University Hospital of Olomouc. The mean age of patients was 61.95 ± 11.02 years. They were split into three groups in accordance with the method of monitoring PA. Group 1 (G1) used a pedometer, group 2 (G2) used a heart rate monitor and group 3 (G3) used both types of equipment simultaneously. Patients recorded the number of steps, the duration of the exercise (G1 and G3) or the average heart rate (G2 and G3), entering this information into the archive system. The checking of monitored indicators took place after 3, 6 and 12 months. RESULTS: The adherence to the programme varied a lot (60-360 days). The results showed that the lowest one was in the case of patients from G1 and the highest one was in the third group of patients. Only 2 patients from group G3 managed to finish the programme (10% of the total number). We found no statistically significant difference between the groups in any of the quality indicators of a physical activity (number of steps, duration of the exercise, estimate of the weekly caloric output and total caloric output during exercise). CONCLUSIONS: Using a pedometer has seemed to be an easy way to monitor the amount of a physical activity. Low adherence to the programme results from a fixation on a sedentary lifestyle, as well as from psychological and social causes. [CÍLE: Cílem studie bylo zhodnotit adherenci k pohybové aktivitě (PA) v rámci ročního intervenčního programu domácí rehabilitace u pacientů po infarktu myokardu. METODIKA: Konečný soubor tvořilo 20 pacientů (4 ženy a 16 mužů) preventivní kardiologie Fakultní nemocnice Olomouc s koronarograficky prokázanou ischemickou chorobou srdeční ve věku 61,95 ± 11,02 let. Podle metodiky kontroly PA byli pacienti rozděleni do tří skupin. Skupina 1 (G1) používala krokoměr, skupina 2 (G2) monitor srdeční frekvence a skupina 3 (G3) oba přístroje současně. Pacienti zapisovali počet kroků, trvání cvičení (G1 a G3) nebo průměrnou srdeční frekvenci (G2 a G3) do záznamových archů. Kontrola sledovaných laboratorních a klinických ukazatelů probíhala po 3, 6 a 12 měsících. VÝSLEDKY: Adherence k programu byla velmi variabilní (60-360 dní), nejnižší byla u pacientů skupiny G2 a nejvyšší ve skupině G3. Program dokončili pouze dva pacienti ze skupiny G3 (10 % z celkového počtu intervenovaných pacientů). Mezi jednotlivými skupinami jsme nezaznamenali statisticky významný rozdíl v žádném ze sledovaných ukazatelů kvality pohybové intervence (počet kroků, doba cvičení, odhad energetické spotřeby při cvičení). ZÁVĚRY: Jako nejvíce akceptovaný prostředek ke kontrole objemu PA se jevil krokoměr. Velmi nízká adherence vyplývá z pevné fixace většinou několik desítek let trvajícího sedavého životního stylu a často má psychologické a sociální příčiny.]